(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The subject of the study was the analysis of short-term seasonal fluctuations in the labour markets in seaside powiats in Poland. The main aim of the study was to determine the size and distribution of seasonal fluctuations in the number of the unemployed and their differentiation according to gender. The study used data of the Local Data Bank and Poviat Labour Offices on the number of registered unemployed for the years 2010-2018. The analyses were based on the deterministic seasonality model. The obtained results indicate that apart from large cities, the seasonality of unemployment in seaside powiats is high. Greater seasonal fluctuations of the unemployment were found in the case of women.